Ensuring the quality of scientific climate policy advice: In an increasingly pragmatic policy environment, advisors should take a step away from politics - Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2015)
The UN climate summit in Paris will bring about a new bottom-up type of agreement based on voluntary emissions reduction pledges by individual states. This marks the end of the top-down policy paradigm dominant for more than two decades. Scientific advisors should use the paradigm shift manifesting itself in UN negotiations as an opportunity to critically reassess their role in international climate policy. In the future, it will become even more difficult to present findings that are both politically viable and scientifically sound. In situations where these standards conflict, advisors and advisory bodies must resist both political pressures and incentives that undermine scientific integrity. (SWP Comments)
Keywords: 320